2009
DOI: 10.1007/s00415-009-0033-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of non-traumatic headache in the emergency department

Abstract: An algorithm based on four clinical scenarios can be administered to the majority of patients presenting to the ED with the chief complaint of NTH. The algorithm showed a good accuracy in identifying patients with non-life threatening causes of headache and could be used as a risk stratification tool to improve clinical decision- making. Further studies are required to validate this diagnostic algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…SAH is a common cause of acute secondary headache in emergency settings [1][2][3][4][5][6]. The present data demonstrated that SAH is also common cause of acute seconddary headache in hospitalized patients.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…SAH is a common cause of acute secondary headache in emergency settings [1][2][3][4][5][6]. The present data demonstrated that SAH is also common cause of acute seconddary headache in hospitalized patients.…”
Section: Discussionsupporting
confidence: 51%
“…However, the underlying causes may change pattern over time particularly where there is rapid social development. Clinical study of acute headache presenting in emergency departments has been previously reported [1][2][3][4][5]. Many acute secondary headaches can be misdiagnosed if appropriate investigations are not made, even life-threatening subarachnoid hemorrhage (SAH) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the ED, non-contrast computed tomography (CT) is the preferred imaging study and is used to rule out hemorrhage, while most patients should perform a magnetic resonance imaging (MRI) brain scan followed by CT/MRI angiography if brain vessel disease is suspected (such as, CAD, aneurysms, and CVST). Lumbar puncture with CSF analysis may help to diagnose SAH, infection, tumor and disorders related to CSF hypertension or hypotension[ 3 , 4 ]. Treatment and prognosis depend on the etiology of the headache.…”
mentioning
confidence: 99%
“…However, in 3.8 – 20% of headache patients, a headache secondary to a potentially life-threatening condition is diagnosed with immediate implications for therapeutic interventions. These include subarachnoidal hemorrhage, cerebral aneurysm, intracranial bleeding, sinus vein thrombosis, temporal arteriitis, or meningitis [ 2 , 5 – 7 ]. It has been shown by various authors that red flags like age >50 years, focal-neurological signs, thunderclap onset of symptoms or altered mental status have a remarkable negative predictive value around 0.98–0.99, however with varying sensitivities (between 0.39 and 100%) and specificities (between 65 and 98%) [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include subarachnoidal hemorrhage, cerebral aneurysm, intracranial bleeding, sinus vein thrombosis, temporal arteriitis, or meningitis [ 2 , 5 – 7 ]. It has been shown by various authors that red flags like age >50 years, focal-neurological signs, thunderclap onset of symptoms or altered mental status have a remarkable negative predictive value around 0.98–0.99, however with varying sensitivities (between 0.39 and 100%) and specificities (between 65 and 98%) [ 7 11 ]. To improve the differentiation of benign headaches from secondary, potentially serious headache forms, various clinical algorithms which include these red flags have been proposed, but they are only inconsistently applied in clinical practice [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%